1999
DOI: 10.1037/1040-3590.11.3.251
|View full text |Cite
|
Sign up to set email alerts
|

A review of recent research addressing the utility of the Rorschach.

Abstract: To address the utility of the Rorschach, the author synthesized a large sample (N = 138) of empirical, quantitative research published in the past 20 years. Longitudinal and behavioral criteria and ecological incremental validity beyond self-report and interview were emphasized because of their relationship with test applications. Methodological issues (temporal consistency, diversity, clinician judgment), applications (treatment outcome, schizophrenia, thought disorder, depression and suicide risk), and selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
214
1
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(226 citation statements)
references
References 194 publications
(277 reference statements)
6
214
1
5
Order By: Relevance
“…The incremental validity and clinical utility of the CS has been seriously questioned Hunsley & Bailey, 1999, while other authors have presented support for the incremental validity and utility of the CS (Blais, Hilsenroth, Castlebury, Fowler, & Baity, 2001;Meyer, 2000;Viglione, 1999) An issue that has been central in the critique of the validity of the CS concerns the meta-analytic studies undertaken primarily to obtain information about the general validity of the Rorschach. There are meta-analytic studies (Atkinson, Quarrington, Alp, & Cyr, 1986;Bornstein, 1999;Hiller, Rosenthal, Bornstein, Berry, & Brunell-Neulib, 1999;Parker, Hanson, & Hunsley, 1988), which are regarded as supporting the validity of the Rorschach.…”
Section: The Rorschach Controversymentioning
confidence: 99%
See 1 more Smart Citation
“…The incremental validity and clinical utility of the CS has been seriously questioned Hunsley & Bailey, 1999, while other authors have presented support for the incremental validity and utility of the CS (Blais, Hilsenroth, Castlebury, Fowler, & Baity, 2001;Meyer, 2000;Viglione, 1999) An issue that has been central in the critique of the validity of the CS concerns the meta-analytic studies undertaken primarily to obtain information about the general validity of the Rorschach. There are meta-analytic studies (Atkinson, Quarrington, Alp, & Cyr, 1986;Bornstein, 1999;Hiller, Rosenthal, Bornstein, Berry, & Brunell-Neulib, 1999;Parker, Hanson, & Hunsley, 1988), which are regarded as supporting the validity of the Rorschach.…”
Section: The Rorschach Controversymentioning
confidence: 99%
“…Proponents and critics of the CS have also debated the temporal consistency and the interrater reliability of the CS (Acklin, McDowell, Verschell, & Chan, 2000;Costello, 1999;Ganellen, 2001;Garb et al, 2001;Hibbard, 2003;Hunsley & Bailey, 1999;Lilienfeld et al, 2000;McDowell & Acklin, 1996;Meyer, 1997aMeyer, , 1997bMeyer et al, 2002;Viglione, 1999;Viglione & Hilsenroth, 2001;Weiner, 2001;Wood, Lilienfeld, Nezworski, & Garb, 2001;Wood, Nezworski, & Stejskal, 1996a, 1996bWood, Nezworski, & Stejskal, 1997). In research, the reliability of the CS variables is now mostly calculated by using the intraclass correlation coefficient, ICC, as recommended by among others Acklin et al (2000).…”
Section: The Rorschach Controversymentioning
confidence: 99%
“…The Comprehensive System (CS; Exner 1974Exner , 2003 provides clinicians with a well-validated and reliable cross-cultural method for scoring and interpreting the Rorschach. Different studies, some of them based on metaanalysis, have confirmed the reliability and validity of Rorschach findings (Society for Personality Assessment 2005), particularly those derived from composite indices (Diener et al 2011;Meyer 2000;Porcelli and Mihura 2010;Viglione 1999;Viglione and Meyer 2008). Empirical research and analyses of case studies that focus on youngsters provide similar evidence for the utility of the Rorschach in predicting psychopathological manifestations, psychiatric severity and treatment outcomes in children and adolescents (Erdberg 2007;Exner and Weiner 1995;Smith et al 2001;Tibon and Rothschild 2007;Viglione 1990).…”
Section: The Utility Of the Rorschach Inkblot Methods For Psychodynamimentioning
confidence: 99%
“…Indeed, there are many studies published in the past 30 years that have examined the link between psychopathology and Rorschach responses. Viglione (1999) concluded that the Rorschach has limitations in its use as a diagnostic instrument, which is a rather generous statement in light of a recent review of the validity of the Rorschach in examining psychiatric diagnoses, by Wood, Lilienfeld, Garb, and Nezworski (2000). Wood et al (2000) examined studies that included diagnoses such as schizophrenia, depression, posttraumatic stress disorder, dissociative identity disorder, dependent personality disorder, narcissistic personality disorder, borderline personality disorder, antisocial personality disorder, and psychopathy.…”
Section: What Constitutes An Appropriate Focus Formentioning
confidence: 99%
“…Having reviewed the evidence presented by Killer, Rosenthal, Bornstein, Berry, and Brunell-Neulieb (1999) and Dawes (1999) and the arguments preferred by Strieker and Gold (1999), Viglione (1999), and Weiner (2001), we have found little reason to alter this position. Indeed, if anything, Garb, Wood, Nezworski, Grove, and Stejskal's (2001) detailed review of the evidence presented in the first Special Section has served to amplify our concerns about the scientific status of the Rorschach.…”
mentioning
confidence: 99%